Detection of viral and bacterial pathogens using multiplex real-time polymerase chain reaction in acute gastroenteritis (Annals of Medical Research, 2021)
Aim: Recently, the syndromic panel-based testing approach has gained popularity in the laboratory diagnosis of gastroenteritis. This study aimed to share our experience in the use of multiplex real-time polymerase chain reaction (PCR) in acute gastroenteritis.Material and Methods: Stool samples were obtained from 86 patients with acute gastroenteritis presenting with fever, bloody diarrhea, and dehydration in Kocaeli and İstanbul between January 2017 and November 2018. The identification was carried out using FTD viral and bacterial gastroenteritis (Fast Track Diagnostics, Luxembourg) kits.Results: The causative agents were identified by multiplex PCR in 53.5% of the samples. A significant relationship was found between the age groups (16-years and older versus under 16-years) and the distribution of agents (p=0.012). A single agent was detected in 41 of 86 samples and co-infection was detected in 5 samples. The most commonly detected viral agents were NorovirusG2, Rotavirus, Astrovirus, Adenovirus, NorovirusG1 and Sapovirus, and for the bacterial agents were Salmonella spp., Shigella spp. EIEC and Campylobacter coli jejuni, verocytotoxin-producing Escherichia coli (VTEC) and Clostridium difficile in orderly.Conclusion: The use of molecular methods may be advised, particularly in high-risk patients. This will ensure the better evaluation of the patients and prevent inappropriate antibiotics usage, as the clinicians are able to resolve diagnostic challenges using more appropriate methods. The validation of diagnostic algorithms that prioritize the testing of certain microorganisms based tests according to their incidence especially in outpatients would seem to be an appropriate first task as a means of avoiding the application of these relatively expensive tests in all patients.
Keywords: Acute gastroenteritis; real-time polymerase chain reaction (PCR); syndromic panel-based testing; viral gastroenteritis; bacterial gastroenteritis